Infectivity of Entomopathogenic Fungal Isolates Against Tarnished Plant Bug Lygus lineolaris (Hemiptera: Miridae). Issue 4 (3rd July 2022) - Maniania, Nguya K; Portilla, Maribel M; Amnulla, Fayaz M; Mfuti, David K; Darie, Andrei; Dhiman, Geetika; Rao, Ishtiaq M
Abstract: Twelve isolates of entomopathogenic fungi belonging to Metarhizium robertsii, M. pinghaense, M. brunneum, Beauveria bassiana, and Isaria fumosorosea were screened against tarnished plant bug. All isolates were pathogenic, causing mortality from 28.8 ± 3.4 to 96.3 ± 2.7%. The LT50 values ranged from 2.7 to 6.0 d while the LT90 values varied between 6.6 and 15.0 d. Metarhizium robertsii isolate CPD6 (will be under the trade name NoVil) was among the isolates that caused high mortality within shorter times and was selected for study on developmental stages and greenhouse trial. The third-, fourth-, and fifth-instar nymphs, and adults were inoculated with 10 6, 10 7, and 10 8 conidia per ml of NoVil. All the stages were susceptible to fungal infection. However, third and fourth instars were the most susceptible with no significant differences in mortality across the three concentrations. On the other hand, mortality was dose-dependent with fifth-instar nymph and adult stages. The LT50 and LT90 values were also dose-dependent, with higher concentrations having shorter lethal-time values as compared to the lower concentrations. In the greenhouse, pepper plants were sprayed with NoVil and chemical insecticide Flonicamid (as industrial standard), before releasing adult tarnished plant bug. Mortality of 37.3, 75.5, and 76.3% was recorded in the control, NoVil, and Flonicamid, respectively. This study has identified NoVil as a potential mycoinsecticide candidate for the control of tarnished plant bug under greenhouse conditions. Further field testing on juvenile and adults is needed to evaluate the potential for in-field control.